Sistem Pengendalian Internal: Analisis Cara Menjaga Persediaan Obat pada Usaha Kecil dan Menengah - Annisa, Annisa; Mubarok, Arif; Himawan, Hilmi Satria; Razikin, M. Khairur (Universitas Palangka Raya, 2024)
To manage inventory well, effective internal control is needed. The application of internal control can be applied to trading companies such as pharmacies. This study aims to determine the suitability of the application of internal control to drug supply according to COSO SME at the X Muara Teweh pharmacy, North Barito Regency. This research was conducted using observation, interview, and documentation techniques. The research subjects were Pharmacy Facility Owners (PSA) and Responsible Pharmacists (APJ). Data analysis was carried out by comparing the COSO SME components with the internal controls implemented by the X Muara Teweh pharmacy and assessing their suitability. The results showed that the X Muara Teweh pharmacy had implemented most of the internal controls in drug supply according to COSO SME. Components that have been implemented include risk assessment, roles and responsibilities, information and communication, and monitoring. Meanwhile, the control environment components and control activities have not been fully implemented according to COSO SME. The urgency of the research was carried out to find out and evaluate internal controls related to the management of drug supplies that have been implemented by pharmacies. The existence of a control component can overcome fraud and other risks. However, the lack of COSO SME information results in the rare implementation of internal control in small and medium-scale companies